Long-Term Trajectory of Recovery Following Pilon Fracture Fixation. Issue 6 (June 2022) - Middleton, Scott D.; Guy, Pierre; Roffey, Darren M.; Broekhuyse, Henry M.; O'Brien, Peter J.; Lefaivre, Kelly A.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To describe the trajectory of recovery following fixation of pilon fractures from baseline to 5-year follow-up. Design: Prospective cohort study. Setting: Level-1 trauma center. Patients/Participants: Patients with pilon fractures (OTA/AO 43.C) treated with open reduction and internal fixation. Intervention: None. Main Outcomes Measures: Patient-reported outcome measures were measured at baseline, 6 months, 1 year, and 5 years using the Short-Form 36 Health Survey (SF-36) Physical Component Score and Mental Component Score, Short Musculoskeletal Functional Assessment, and the Foot and Ankle Outcome Score. Results: One hundred two patients were enrolled: mean age was 42.6 years; 69% were males; 88% had an injury severity score of 9; 74 patients (73%) completed 1-year follow-up; 40 patients (39%) completed 5-year follow-up. Trajectory of recovery of physical function showed a significant decline between baseline and 6 months, with significant improvement between 6 months and 1 year and then ongoing but slower improvement between 1 year and 5 years. Sixty-four patients returned to baseline SF-36 Physical Component Score at 5 years. Pain was a persistent issue and remained significantly worse at 5 years when compared with baseline. Psychological well-being (SF-36 Mental Component Score) did not significantly change from baseline at 5 years. Conclusion: Functional recovery following open reduction and internal fixation for pilon fractures was characterized by an initial decrease in function from baseline, followed by an increase between 6 months and 1 year, and then slower but continued increases from 1 year to 5 years. Function did not return to baseline levels, pain was a persistent issue, and mental well-being showed no change from baseline at 5 years. This information may be useful when counselling patients. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.